1996
DOI: 10.1042/bst024569sa
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Condensation During Apoptosis Requires Atp

Abstract: The processes leading to morphological changes of the chromatin in cells that undergo apoptosis are presently unclear. We have recently shown that chromatin fragmentation and the nuclear morphological changes typically seen in apoptosis were reproduced in an in itro system comprised of isolated rat thymocyte nuclei incubated in the presence of a lysate from Fas\APO-1-stimulated JURKAT cells [Chow, Weis, Kass, Holmstro$ m, Eriksson and Orrenius (1995) FEBS Lett. 364, [134][135][136][137][138]. Using this in itr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
5

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 22 publications
1
55
1
5
Order By: Relevance
“…Although the morphological characteristics of apoptosis have been described in detail (Arends and Wyllie 1991), little is know about the mechanisms responsible for chromatin condensation except that it shows an absolute requirement for ATP, as recently reported by Kass et al (1996). In vitro, the ability of PA to condense DNA and to facilitate DNA conformational changes is well established (for review see Marton and Morris 1987).…”
Section: Discussionmentioning
confidence: 94%
“…Although the morphological characteristics of apoptosis have been described in detail (Arends and Wyllie 1991), little is know about the mechanisms responsible for chromatin condensation except that it shows an absolute requirement for ATP, as recently reported by Kass et al (1996). In vitro, the ability of PA to condense DNA and to facilitate DNA conformational changes is well established (for review see Marton and Morris 1987).…”
Section: Discussionmentioning
confidence: 94%
“…[6][7][8][9][10][11] Severe (but not complete) depletion of ATP resulted in that certain typical apoptotic stimuli initiated necrosis instead of apoptosis, [7][8][9][10][11] whereas complete ATP exhaustion gave rise to a third type of cell death differing from both apoptosis and necrosis ("energy catastrophe"). 11 This indicates that not only apoptosis but also necrosis requires some ATP.…”
Section: Atp-dependent Steps Of Apoptosismentioning
confidence: 99%
“…Lack of energy converts apoptosis to necrosis [16,17]. The release of cyto-c from mitochondria, observed in both the apoptotic initiation pathways (intrinsic and extrinsic), should promote impairment in the oxidative phosphorylation process in relation to the amount of cyto-c released into the cytosol.…”
Section: Commentmentioning
confidence: 99%
“…The existence of the cytosolic NADH/cyto-c electron transport pathway was uncovered in 1991 [11] before the finding reported in 1996 that, in physio-pathological conditions, cyto-c can be released into the cytosol where it becomes a fundamental component of the apoptotic cell death program [15]. Thereafter we proposed, and continue to maintain, that in apoptotic cells, with an increased level of cyto-c in the cytosol and the impairment of the respiratory chain, the activity of the NADH/cyto-c system, coupled with the generation of an electrochemical proton gradient [12,13], may represent an additional but necessary source of energy required for the correct execution of the death program [16,17]. Very recently we have reported that in liver mitochondria along with the release of cyto-c, ceramide, a well known inducer of apoptosis, promotes, the stimulation of the cytosolic NADH/cyto-c electron transport activity coupled with an increased generation of DWm useful for ATP synthesis [18].…”
Section: Introductionmentioning
confidence: 96%